2001
DOI: 10.1007/s004380100484
|View full text |Cite
|
Sign up to set email alerts
|

A family of DNA repeats in Aspergillus nidulans has assimilated degenerated retrotransposons

Abstract: In the course of a chromosomal walk towards the centromere of chromosome IV of Aspergillus nidulans, several cross-hybridizing genomic cosmid clones were isolated. Restriction mapping of two such clones revealed that their restriction patterns were similar in a region of at least 15 kb, indicating the presence of a large repeat. The nature of the repeat was further investigated by sequencing and Southern analysis. The study revealed a family of long dispersed repeats with a high degree of sequence similarity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Experimental evidence has subsequently shown that RIP, as an active process, exists in many other ascomycetes, including Magnaporthe grisea (Nakayashiki et al 1999; Ikeda et al 2002), Podospora anserina (Graïa et al 2001), and Leptosphaeria maculans (Idnurm and Howlett 2003). Mutation patterns indicative of RIP, that is, elevated rates of transition mutations of cytosines in the context of particular surrounding nucleotides, have been observed in repetitive elements from Fusarium oxysporum (Hua-Van et al 1998), Penicillium chrysogenum (Braumann et al 2008), Nectria haematococca (Coleman et al 2009), Grossmannia clavigera (DiGuistini et al 2011), and several Neurospora (Kinsey et al 1994) and Aspergillus species (Neuveglise et al 1996; Nielsen et al 2001; Montiel et al 2006; Braumann et al 2008; Clutterbuck 2011). Though the RIP process causes C-to-T transitions in each of these species, there is substantial variation in the preferred adjacent nucleotide context for RIP mutations (reviewed in Galagan and Selker 2004; Clutterbuck 2011), which may be a consequence of coevolutionary dynamics between the RIP defense and the TEs.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence has subsequently shown that RIP, as an active process, exists in many other ascomycetes, including Magnaporthe grisea (Nakayashiki et al 1999; Ikeda et al 2002), Podospora anserina (Graïa et al 2001), and Leptosphaeria maculans (Idnurm and Howlett 2003). Mutation patterns indicative of RIP, that is, elevated rates of transition mutations of cytosines in the context of particular surrounding nucleotides, have been observed in repetitive elements from Fusarium oxysporum (Hua-Van et al 1998), Penicillium chrysogenum (Braumann et al 2008), Nectria haematococca (Coleman et al 2009), Grossmannia clavigera (DiGuistini et al 2011), and several Neurospora (Kinsey et al 1994) and Aspergillus species (Neuveglise et al 1996; Nielsen et al 2001; Montiel et al 2006; Braumann et al 2008; Clutterbuck 2011). Though the RIP process causes C-to-T transitions in each of these species, there is substantial variation in the preferred adjacent nucleotide context for RIP mutations (reviewed in Galagan and Selker 2004; Clutterbuck 2011), which may be a consequence of coevolutionary dynamics between the RIP defense and the TEs.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only the two fungal species, both of which are classified into the same order Sordariales, are clearly proven to have the RIP mechanism. RIP-like C:G to T:A transitions are, however, also reported in the sequence of transposable elements in several phylogenetically more distant filamentous fungi, including Aspergillus fumigatus (Neuveglise et al ., 1996), Aspergillus nidulans (Nielsen et al ., 2001), Fusarium oxysporum (Julien et al ., 1992;Hua-van et al ., 1998) and Magnaporthe grisea (Nakayashiki et al ., 1999a) . Interestingly, some of them have no known sexual stage (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, (A/Tp)Cp(A/T) in M. grisea (Nakayashiki et al ., 1999a), Cp(A/G) in F. oxysporum (Hua-van et al ., 1998) and CpG in A . fumigatus and A. nidulans (Neuveglise et al ., 1996;Nielsen et al ., 2001) . Therefore, it is not clear whether the RIP-like transitions found in those fungi were operated by processes equivalent to RIP or not.…”
Section: Introductionmentioning
confidence: 99%
“…First discovered in Neurospora crassa [1,2], RIP was later demonstrated in the Ascomycetes Magnaporthe oryzae [3,4], Podospora anserina [5], Leptosphaeria maculans [6] and Fusarium graminearum [7]. Putative RIP events have also been detected bioinformatically in Aspergillus fumigatus [8], Fusarium oxysporum [9-11], Aspergillus nidulans [12], Neurospora tetrasperma [13], Microbotryum violaceum [14], Aspergillus oryzae [15], Magnaporthe oryzae [16], Colletotrichum cereal [17], Aspergillus niger [18], Penicillium chysogenum [18] and most recently in Stagonospora nodorum [19,20]. Given this broad distribution, it is reasonable to assume that RIP is widespread across, but so far restricted to, filamentous ascomycota and basidiomycota.…”
Section: Introductionmentioning
confidence: 99%
“…RIP increases the frequency of particular di-nucleotides (TpA in most cases studied to date) in affected regions of DNA. Thus RIP can be identified by comparing ratios of di-nucleotide frequencies in pre-RIP to post-RIP sequences; these ratios are referred to as "RIP indices" [8,12,25,26]. However, in reality RIP depends upon the alignment of two similar regions of double-stranded DNA [23] and therefore it is more appropriate to use alignments of repeat families to identify and quantify RIP.…”
Section: Introductionmentioning
confidence: 99%